Possible routes of entry into the country for African swine fever – Risk profile - Finnish Food Safety Authority (Zenodo, 2011)
The African swine fever is a viral disease that spreads easily to domestic pigs and wild boar and has considerable socioeconomic consequences as well. The disease occurs as well as in domestic pigs as in wild boar in the largest part of sub-Saharan Africa and in Sardinia. Since 2007 the disease has occurred in the Caucasus region and in 2011 near the border of Finland: the Leningrad region and the Kola Peninsula. In the risk profile different routes and chains of events which could lead to the African swine fever entering Finland for the first time are identified and described. The most obvious ones are: people who have travelled in the infected area, infected meat or meat products, with domestic pigs and sperm, contaminated transport vehicles, catering waste from international transport and infected wild boars crossing the border to Finland. The key measures to protect the Finnish swine industry from the African swine fever are high biosecurity of farms and effective and aimed information on the risks of the disease. FI; en; efsafocalpoint@evira.fi